The topical problems of the improvement of juridical education - A. M. Tsaliev (Высшее образование в России, 2022)
The article considers the topical issues concerning the improvement of the quality of the legal education. Special attention is paid to the educational program, namely inclusion of thediscipline “human rights”, and to the forms of knowledge control.